Efficacy and safety of bevacizumab for the treatment of advanced hepatocellular carcinoma: a systematic review of phase II trials. - Ping Fang; Jin-hua Hu; Zhi-gang Cheng; Zhe-feng Liu; Jin-liang Wang; Shun-chang Jiao (PLoS ONE)
Background Hepatocellular carcinoma (HCC) is a common cancer associated with a poor prognosis. Bevacizumab is a monoclonal antibody that binds vascular endothelial growth factor, a mediator of tumor angiogenesis. Bevacizumab is currently under investigation as treatment for HCC. We performed a systematic review of the efficacy and safety of bevacizumab for the treatment of advanced HCC. Methods PubMed, the Cochrane Library, and Google Scholar were searched using the terms "bevacizumab AND hepatocellular carcinoma AND (advanced OR unresectable)". Phase II trials of bevacizumab for the treatment of advanced HCC were included. Outcomes of interest included progression-free and overall survival (PFS and OS), tumor response, and toxicities. Results A total of 26 records were identified. Of these, 18 were excluded. Hence, eight trials involving 300 patients were included. Bevacizumab was given as monotherapy (n = 1 trial) or in combination with erlotinib (n = 4 trials), capecitabine (n = 1 trial), capecitabine+oxaliplatin (n = 1 trial), or gemcitabine+oxaliplatin (n = 1 trial). Most trials (five of eight) reported median PFS and OS between 5.3 months and 9.0 months and 5.9 and 13.7 months, respectively. The disease control rate was consistent in five of eight trials, ranging from 51.1% to 76.9%. The response and partial response rates ranged from 0 to 23.7%, but were around 20% in four trials. Only one patient had a complete response. Frequently reported Grade 3/4 toxicities were increased aspartate transaminase/alanine transaminase (13%), fatigue (12%), hypertension (10%), diarrhea (8%), and neutropenia (5%). Thirty patients experienced gastrointestinal bleeding (grade 1/2 = 18, grade 3/4 = 12), typically due to esophageal varices. Conclusions Bevacizumab shows promise as an effective and tolerable treatment for advanced HCC. The reported efficacy of bevacizumab appears to compare favorably with that of sorafenib, the only currently approved treatment for unresectable HCC. Phase III trials are warranted to comprehensively examine the efficacy and safety of bevacizumab for treatment of advanced HCC.